International Multispecialty Consensus on How to Image, Define, and Grade Ultrasound Imaging Features of First Metatarsophalangeal Joint Osteoarthritis, a Delphi Consensus Study - Molyneux, P; Bowen, C; Ellis, R; Rome, K; Carroll, M (Elsevier BV, 2023)
Objective To reach consensus concerning which ultrasound imaging features should be assessed and graded, and what ultrasound imaging procedure should be performed when examining osteoarthritic change in the first metatarsophalangeal joint. Design An online Delphi study was conducted over four iterative rounds with 16 expert health professionals. Items were scored from 0-100 (0 = not at all important; 100 = extremely important). Consensus was defined based upon an item receiving a median score of ≥70% acceptance. Items receiving median score of ≤50% were rejected. Items considered ambiguous (median score 51% - 69% of acceptance) were assessed in an additional round. A final round determined the content validity of items through calculation of the content validity ratio and content validity index. Results Sixteen items were deemed essential, which included osteophytes graded dichotomously, cartilage damage graded continuously, synovitis and joint space narrowing graded on a semiquantitative scale. The panel deemed essential that the first metatarsophalangeal joint start in a neutral position, then move through range of motion for both dorsal and plantar scanning, orientating the probe in longitudinal and in transverse, whilst using first metatarsal head and proximal phalanx as anatomical landmarks. A supine body position was only deemed essential for a dorsal scan and a neutral foot/ankle position was only rated essential for a plantar scan. The content validity index of the 16 essential items was 0.19. Conclusion The consensus exercise has identified the essential components the ultrasound imaging acquisition procedure should encompass when examining first metatarsophalangeal joint osteoarthritis.
Keywords: Osteoarthritis; Metatarsophalangeal Joint; Ultrasound imaging; Foot